The gender paradox in pro-environmental engagement: Actionable insights for cause-related marketing and social advocacy campaigns - Borau, Sylvie; Mai, Robert (Journal of the Academy of Marketing Science, 2026)
Abstract The growing gender polarization in consumers’ pro-environmental engagement—with women more engaged than men—suggests that organizations should consider gender a key criterion when targeting their cause-related marketing and social advocacy campaigns for environmental causes. However, multilevel analyses of 11 behavioral interventions across 63 countries ( N = 56,582) reveal that relying on gender alone is insufficient and can even backfire, uncovering a surprising paradox: The gender gap in pro-environmental engagement widens among liberal consumers, in societies with higher gender equality, and cultures emphasizing care over competition. These gender paradoxes emerge when identities and societal contexts intersect, revealing why interventions ignoring such complexities can fail. Results show that a collective action framing is effective across several identity combinations, while a negative emotional appeal can backfire, particularly among conservative men in gender-equal countries. A web-based tool helps marketers and policymakers select effective environmental interventions across intersecting individual and country-level factors, enabling targeted advocacy and cause-related marketing.